Influence of organic compost on the growth of choy sum (Brassica rapa var parachinensis) and pak choi (Brassica rapa var chinensis) - Nur Aqazah Bungsu
Soil fertility is important for sustainable crop production. Chemical fertilizers are expensive and can bring a negative impact to the soil in the long term. Organic compost can act as an alternative way to overcome this problem. Therefore, a study was carried out to investigate the influence of organic compost (vegetable waste mixed with goat dung) on the growth of choy sum (Brassica rapa var parachinensis) and pak choi (Brassica rapa var chinensis) under nursery condition in University Malaysia Kelantan, Jeli campus. The bioassay species were treated with commercial NPK fertilizer and organic compost at an application rate of 250 kg ha-1 and 15000 kg ha-1, respectively while control at 0 kg ha-1. The result from this study showed the stimulating effect from the treatment of organic compost to choy sum and pak choi. The parameters of plant height, plant weight and chlorophyll content for choy sum and pak choi are significantly increased (P≤0.05) while the root length shows insignificant results (P≤0.05) compared to control. Thus, this study proved that the maximum growth of choy sum (Brassica rapa var parachinensis) and pak choi (Brassica rapa var chinensis) were successfully achieved when the plants were supplemented with organic compost which is vegetable waste mixed with goat dung. Even though commercial NPK fertilizer shows the similar effect to organic compost, the organic compost exhibit higher value in increased the growth of choy sum and pak choi. To conclude, the overall results of the study indicate that the compost of vegetables waste mixed with goat dung can be applied and used to ensure the healthier and vigorous growth of choy sum and pak choi.